Understanding the dynamics of sustainable change: A 20-year case study of integrated health and social care - Charlotte Klinga; Henna Hasson; Magna Andreen Sachs; Johan Hansson (BMC, 2018)
Abstract Background Change initiatives face many challenges, and only a few lead to long-term sustainability. One area in which the challenge of achieving long-term sustainability is particularly noticeable is integrated health and social care. Service integration is crucial for a wide range of patients including people with complex mental health and social care needs. However, previous research has focused on the initiation, resistance and implementation of change, while longitudinal studies remain sparse. The objective of this study was therefore to gain insight into the dynamics of sustainable changes in integrated health and social care through an analysis of local actions that were triggered by a national policy. Methods A retrospective and qualitative case-study research design was used, and data from the model organisation's steering-committee minutes covering 1995-2015 were gathered and analysed. The analysis generated a narrative case description, which was mirrored to the key elements of the Dynamic Sustainability Framework (DSF). Results The development of inter-sectoral cooperation was characterized by a participatory approach in which a shared structure was created to support cooperation and on-going quality improvement and learning based on the needs of the service user. A key management principle was cooperation, not only on all organisational levels, but also with service users, stakeholder associations and other partner organisations. It was shown that all these parts were interrelated and collectively contributed to the creation of a structure and a culture which supported the development of a dynamic sustainable health and social care. Conclusion This study provides valuable insights into the dynamics of organizational sustainability and understanding of key managerial actions taken to establish, develop and support integration of health and social care for people with complex mental health needs. The service user involvement and regular reviews of service users' needs were essential in order to tailor services to the needs. Another major finding was the importance of continuously adapting the content of the change to suit its context. Hence, continuous refinement of the change content was found to be more important than designing the change at the pre-implementation stage.